2020
DOI: 10.3389/fmed.2020.00512
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Description of Hyponatremia in a Swiss Tertiary Care Hospital: An Observational Retrospective Study

Abstract: Background: Hyponatremia (serum sodium concentration <135 mEq/L) is the most common electrolyte abnormality among hospitalized patients. Our aim was to study the epidemiology of hyponatremia in hospitalized patients, as well as the short-term mortality rates, the length of stay (LOS), and associated hospital costs. Methods: This retrospective cohort study included 6,539 hospitalizations in the internal medicine ward of a Swiss tertiary-care teaching hospital between January 1, 2012, and December 31, 2018 (42.7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 28 publications
0
10
0
3
Order By: Relevance
“…Hyponatremia (serum sodium levels <135 mmol/L) is the most common fluid and electrolyte imbalance in hospitalized patients [1]. It is more frequent among geriatric patients, with an estimated prevalence in hospitalized patients up to 32.5% [1]. The presence of hyponatremia in older patients is associated with impaired cognition, delirium, and a higher incidence of falls and fractures [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hyponatremia (serum sodium levels <135 mmol/L) is the most common fluid and electrolyte imbalance in hospitalized patients [1]. It is more frequent among geriatric patients, with an estimated prevalence in hospitalized patients up to 32.5% [1]. The presence of hyponatremia in older patients is associated with impaired cognition, delirium, and a higher incidence of falls and fractures [2].…”
Section: Introductionmentioning
confidence: 99%
“…Hyponatremia (serum sodium levels <135 mmol/L) is the most common fluid and electrolyte imbalance in hospitalized patients [ 1 ]. It is more frequent among geriatric patients, with an estimated prevalence in hospitalized patients up to 32.5% [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, there are conflicting results regarding the association between gender and the prevalence of hyponatremia. For instance, unlike the Swiss study, hyponatremia was higher in females in the US study [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 71%
“…The association between hyponatremia and patient characteristics such as age and gender has been investigated thoroughly. The results have shown that the prevalence of hyponatremia increases with age [8][9][10]. However, there are conflicting results regarding the association between gender and the prevalence of hyponatremia.…”
Section: Introductionmentioning
confidence: 99%
“…Hyponatremia is a common electrolyte among hospitalized patients that poses diagnostic and therapeutic challenges. A recent retrospective study associated persistent hyponatremia with increased length of stay, readmissions, and mortality [ 1 ]. Accurate diagnosis of the etiology of hyponatremia is dependent on an understanding of water homeostasis [ 2 ].…”
Section: Introductionmentioning
confidence: 99%